Examination of Sexual Quality of Life and Dyadic Adjustment among Women with Mastectomy - GÜRKAN, AYSEL (AVES, 2020)
Objective: To investigate the effect of mastectomy on sexual quality of life and dyadic adjustment among women with breast cancer. Materials and Methods: This study was carried out in an analytical and retrospective way by comparing women with mastectomy and the control group who had similarities to this group and did not have breast cancer. The study included 88 women who underwent mastectomy surgery at least 1 year and at most 5 years ago and 88 women who did not undergo mastectomy with matching ages and levels of education. The data were collected using the Individual Characteristics Form, Sexual Quality of Life-Female, and the Dyadic Adjustment Scale for women with and without mastectomy. Results: In both groups sexual quality of life and dyadic adjustment were positively correlated. Sexual quality of life and dyadic adjustment of women with mastectomy were significantly lower compared to the control group. It was found that sexual quality of life improved as the education level of women with mastectomy increased. Also, sexual quality of life and dyadic adjustment were significantly higher in women with mastectomy whose income was equal to or greater than their expenditures compared to those with income lower than expenditures. Conclusion: Sexual quality of life and dyadic adjustment of women with mastectomy are low than women without mastectomy. Nurses should to assess the risk of low dyadic adjustment and sexual quality of life, educate and consultant women on how they can maintain healthy sexual relationships and dyadic adjustment with their spouse after mastectomy.
Keywords: Breast cancer; mastectomy; sexual quality of life; dyadic adjustment; BREAST-CANCER; YOUNGER WOMEN; BODY-IMAGE; DYSFUNCTION